2017
DOI: 10.1016/j.jscs.2017.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel synthesis of highly TiO2 aerogel photocatalyst via high temperature supercritical drying

Abstract: Nanocrystalline powders of TiO 2 xerogel and aerogel were prepared by using acidmodified sol-gel approach. For TiO 2 aerogel material (TA), the solvent was high temperature supercritically extracted at 300°C and 100 bars. However, the TiO 2 xerogel material (TX) was dried at 200°C and ambient pressure. The effects of the drying processes on the crystalline structure, phase transformation and grain growth were determined by Raman spectroscopy, SAED and Xray diffraction (XRD) analyses using Rietveld refinement m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…In the inset BJH pore size distribution curves [32]. The band located at 1430 cm −1 is assigned to the νs (COO) symmetric stretching vibrations of the acetic acid group coordinated to Ti as a bidentate acetate ligands [33,34]. The bands for Ti-O-Ti and Ti-O bonds are present in the 400-1100 cm -1 region, the former being observed in a very large wavenumber region [35].…”
Section: Resultsmentioning
confidence: 99%
“…In the inset BJH pore size distribution curves [32]. The band located at 1430 cm −1 is assigned to the νs (COO) symmetric stretching vibrations of the acetic acid group coordinated to Ti as a bidentate acetate ligands [33,34]. The bands for Ti-O-Ti and Ti-O bonds are present in the 400-1100 cm -1 region, the former being observed in a very large wavenumber region [35].…”
Section: Resultsmentioning
confidence: 99%
“…Also, TiO 2 aerogel systems with a single-phase anatase and high crystallinity were obtained by supercritical drying in CO 2 , while the ambient pressure drying process resulted in a mixture of anatase and rutile phases . In another study, TiO 2 aerogels demonstrated better photocatalytic degradation due to the higher crystallinity grade than their xerogel counterparts …”
Section: Resultsmentioning
confidence: 99%
“…59 In another study, TiO 2 aerogels demonstrated better photocatalytic degradation due to the higher crystallinity grade than their xerogel counterparts. 60…”
Section: Inorganic Chemistrymentioning
confidence: 99%
“…Solvent composition and solvent quantity were investigated to keep the silica dissolution as low as possible during the supercritical drying; operating in this way, silica aerogels with densities lower than 3 kg/m 3 were obtained. Moussaoui et al [ 49 ] synthesized TiO 2 aerogels for photocatalysis applications. In this case, isopropanol was supercritically extracted at 300 °C and 100 bar.…”
Section: Classificationmentioning
confidence: 99%